2022
DOI: 10.5380/ce.v27i0.79533
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Toxicidade Financeira (Facitcost) De Pacientes Com Câncer No Sul Do Brasil

Abstract: Objetivo: avaliar a toxicidade financeira e correlacionar o escore total com as características sociodemográficas e clínicas de pacientes com câncer assistidos em instituições pública e privada. Método: estudo transversal descritivo, realizado entre setembro de 2018 a janeiro de 2020 com 126 pacientes em tratamento quimioterápico no estado do Paraná, Brasil. Utilizou-se instrumento sociodemográfico e clínico e COmprehensive Score for financial Toxicity; para análise, o teste t de Student e Scoring Guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…With regard to lifestyle, among participants in this study with moderate and high FT levels, more than half used continuous medication. Similar data was found in a study ( 6 ) with people with cancer, which found that, of the total number of participants, 60.32% used frequent medication.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…With regard to lifestyle, among participants in this study with moderate and high FT levels, more than half used continuous medication. Similar data was found in a study ( 6 ) with people with cancer, which found that, of the total number of participants, 60.32% used frequent medication.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to family income in this study, a quarter of the participants had an income between one and two minimum wages, a value that can show FT, even though care is provided by the public health system. Another study carried out in Brazil with people with cancer identified that the lower the purchasing power, the higher the FT ( 6 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations